سوسولوجيا اللغة في المجتمع الجزائري المعاصر "التنوعات اللغوية والممارسات اللسانية " - حسني, هنية (دفـاتر المـــــــــــخبـر, 2018)
ملخص : ينتمي هذا الطرح إلى الدراسات السوسيو-لسانية، حيث يتناول هذا الأخير علاقة بنية اللغة والمجتمع، ومختلف التبيونات الثقافية اللغوية والاجتماعية التي تميز المجتمعات المتعددة الثقافات واللغات.كمجتمعات الشمال الإفريقي؛ والتي من بينها الجزائر؛ حيث تميزت الجزائر بالتنوع الثقافي واللساني على الامتداد الجغرافي الذي حددها، وذلك منذ الوجود الأول للعنصر البشري في الجزائر. لذلك أردنا في هذا الطرح المتواضع التعرف ولو بشكل مختصر عن طبيعة وشكل هذا التنوع اللغوي وعلاقته بالهوية اللهوية لهذا المجتمع من حيث الممارسة اللسانية لأفراد المجتمع، ومن حيث الاعتراف الاجتماعي بهذه اللغات. Abstract: This thesis is part of the Socio-Linguistic Studies. It deals with the relationship between the structure of language and society, and the various linguistic and social linguistic adaptations that characterize multicultural societies and languages. Such as Algeria, where Algeria has been characterized by cultural and linguistic diversity over its geographical extension since the first human presence in Algeria. So we wanted in this humble proposition. To identify even briefly, the nature and form of this linguistic diversity and its relationship to the identity of God for this community in terms of the linguistic practice of members of society, and in terms of social recognition of these languages.